New Research in Multimedia and Internet Systems - Zgrzywa, Aleksander (Springer, 2015)
The rapid proliferation of Multimedia and Network Information Systems is one of the key features of our times. What is also important is that the pace of change is ever increasing. University projects of today will form the core of consumer products of tomorrow.